THE ANALYSIS OF THE RELATIONS BETWEEN STOCK RETURNS AND SOME MACRO-ECONOMICS FACTOR: INFLATION, EXCHANGE RATE, AND INTEREST RATE OF BANK INDONESIA CERTIFICATE (SBI) BY INDUSTRIAL SECTOR DURING THE PERIOD OF 2006-2008 IN INDONESIA - MACHETTY (NIM : 29107392); Pembimbing : Dr. Ir. Sudarso Kaderi Wiryono, OCTAFIANA
This study examines three macro-economic factors (inflation, exchange rate, and interest rate of SBI) that influence the stock retursn. Object of this study are companies in 9 industrial sectors that listed in the Indonesia Stock Exchange, with the historical prices for the period of 2006-2008. A total of 252 stocks were studied, and 12 stocks have been excluded from this study due to insufficient data available. Stock return measured by the precentage of the difference of closing-price every month divided by the initial stock price. The macro-economic factors that expected had relations with the stock return are inflation, exchange rate, and interest rate of SBI. The data of inflation, and interest rate of SBI was taken by monthly period, and data for the exchange rate is the buying-prices. Data were analized by multiple-regression using SPSS program. Observations were analyzed year-by-year and during three years. The result shows those three factors of the macro-economics have no significant influence toward return stock in 2006 and 2007. However, in 2008, inflation, exchange rate, and interest rate of SBI, have significant influence only in one industrial sector that is “Property and Real Estate”. The result during three years, shows those three factors of the macro-economics have significant influence to almost all industrial sectors.